2015
DOI: 10.1038/srep09188
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of macrophage - cancer cell crosstalk in estrogen receptor positive and triple-negative breast cancer

Abstract: Tumor heterogeneity may broadly influence the activation of tumor-associated macrophages. We aimed to dissect how breast cancer cells of different molecular characteristics contribute to macrophage phenotype and function. Therefore, we performed whole transcriptome sequencing of human monocytes that were co-cultured with estrogen receptor positive (ER+) or triple-negative (TNBC) breast cancer cell lines and studied the biological responses related to the differential gene activation in both monocytes and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 41 publications
10
104
0
Order By: Relevance
“…We showed that upon S100A4 stimulation, basal‐like BCCs secrete factors that trigger monocyte‐to‐macrophage differentiation and polarization. This is in line with previous studies demonstrating that basal‐like/TNBC, compared to luminal BC, have superior abilities to recruit macrophages (Espinoza et al ., 2016; Sousa et al ., 2015), modulate their polarization, and stimulate protumorigenic functions (Hollmen et al ., 2015; Sousa et al ., 2015; Stewart et al ., 2012; Su et al ., 2014). The current study adds to the previous knowledge by revealing a strong potentiating influence of S100A4, which is expressed at elevated levels in basal‐like/TNBC as also reported previously (Egeland et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that upon S100A4 stimulation, basal‐like BCCs secrete factors that trigger monocyte‐to‐macrophage differentiation and polarization. This is in line with previous studies demonstrating that basal‐like/TNBC, compared to luminal BC, have superior abilities to recruit macrophages (Espinoza et al ., 2016; Sousa et al ., 2015), modulate their polarization, and stimulate protumorigenic functions (Hollmen et al ., 2015; Sousa et al ., 2015; Stewart et al ., 2012; Su et al ., 2014). The current study adds to the previous knowledge by revealing a strong potentiating influence of S100A4, which is expressed at elevated levels in basal‐like/TNBC as also reported previously (Egeland et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This cluster harbors several chemoattractive cytokines many of which previously have been associated with tumorigenesis primarily through generation of a tumor-promoting proinflammatory microenvironment (Figure 1a, refs 10, 11, 12). …”
Section: Introductionmentioning
confidence: 98%
“…[3] In the last few decades, with the development of 2D cells co-cultures, these models gained the ability to better represent the cellular heterogeneity found in different human tissues. For instance, tumor cellular heterogeneity has been mimicked by seeding cancer cells along with stem-like cells, [4] fibroblasts, [5] macrophages, [6] among others. Additionally, the central nervous system architecture has been reproduced by growing embryonic cortical neurons in the presence of cortical microglia, [7] while hepatocyte/Kupffer cells co-cultures have been used to study immune-related responses to drugs.…”
Section: Introduction: Spheroids As 3d Tumor Tissue Culture Modelsmentioning
confidence: 99%